2016
DOI: 10.1002/2016jd025055
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment of the summertime marine atmospheric boundary layer to the western Iberia coastal morphology

Abstract: During summer (June, July, and August), northerly winds driven by the Azores anticyclone are prevalent over western Iberia. The Quick Scatterometer Satellite 2000 to 2009 summertime estimates reveal a broad high wind speed (≥7 ms−1) area extending about 300 km from shore and along the entire Iberian west coast. Nested in this large high‐speed region, preferred maximum regions anchored in the Iberian major capes, Finisterre, Roca, and S. Vicente, are found. Composite analyses of wind maxima were performed to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…These higher IPCJ occurrence areas, where the wind speed at the surface and at the lower atmosphere is also highest, were also recently mapped by Monteiro et al . () using remote sensing QuickSCAT measurements.…”
Section: Introductionmentioning
confidence: 99%
“…These higher IPCJ occurrence areas, where the wind speed at the surface and at the lower atmosphere is also highest, were also recently mapped by Monteiro et al . () using remote sensing QuickSCAT measurements.…”
Section: Introductionmentioning
confidence: 99%
“…It is hypothesized that this maximum is due to the bend in Iberia coast in a similar way as reported by Edwards et al () for California and by Patricola and Chang () for the Benguela region. The southern regime is characterized by the smaller Roca and/or S. Vicente expansion fans that are a hydraulic response to topography, as described for the California coast by (Dorman et al, ; Dorman & Koračin, ; Winant et al, ) and previously for Iberian coast by (Monteiro, Santos, et al, ; Rijo et al, ; Soares et al, ).…”
Section: Discussionmentioning
confidence: 72%
“…ASCAT‐6.25 evening passes show wind intensification frequencies of about 21% and 18% at Finisterre and Roca, and close to 28% at S. Vicente. In a previous study using QuikSCAT during the summers of 2000 to 2009 Monteiro, Santos, et al () found that S. Vicente intensifications occur less often (18%).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations